PENGARUH BAURAN PEMASARAN TERHADAP PERMINTAAN DODOL KETAN HITAM ( KASUS DI UD. WARNASARI SURANADI LOMBOK BARAT) - IDA AYU NOPIARI; YEZKHIAL UMBU PINGGE; I DEWA GEDE SUARTHA; MADE SUMA WEDASTRA (GANEC SWARA, 2021)
This study aims to determine the effect of the marketing mix (product, price, promotion, location, service, process, physical evidence) simultaneously affects the demand for black sticky rice dodol and to determine the effect of the marketing mix (product, price, promotion, location, service, process, physical evidence) partially affect the demand for black sticky rice dodol at UD. Warnasari Suranadi, West Lombok.The research location was conducted at UD. Warnasari Lombok Barat purposively determined on the basis of the company's strategic location and has regular customers/consumers throughout the year. The number of respondents who were taken were 60 people, the determination of which was done by proportional random sampling as much as 25%.The results showed that the marketing mix (product, price, promotion, location, service, process, physical evidence) simultaneously had a significant effect on the demand for black sticky rice dodol. Similarly, the marketing mix (product, price, promotion, location, service, process, physical evidence) partially affects the demand for black sticky rice dodol at UD. Warnasari Suranadi, West Lombok.Based on the results of these studies, it can be suggested: producing types of quality products and varied designs to attract consumer interest and to increase promotions by making advertisements/images more attractive and attractive, and using promotional media that are easily accessible to the public.